The Effect of Knowledge Protection Process on Employee Performance of PT. Mitra Kerinci - Ondi, Ondi (Business and Investment Review, 2023)
This study aims to find out and analyze the influence of the knowledge management process seen from knowledge protection on the performance of PT. Mitra Kerinci. This research is a causative study with quantitative methods. This study uses a nonprobability sampling technique with a purposive sampling method, the criteria used are permanent employees (Permanent / PKWTT) with a working period of more than 5 years. The results of the study show that the knowledge management process seen from knowledge protection has a positive and not significant effect on the performance of employees of PT. Mitra Kerinci. AbstrakPenelitian ini bertujuan untuk mengetahui dan menganalisis pengaruh proses manajemen pengetahuan yang dilihat dari knowledge protection terhadap kinerja karyawan PT. Mitra Kerinci. Penelitian ini merupakan penelitian kausatif dengan metode kuantitatif. Penelitian ini menggunakan teknik pengambilan sampel secara non probabilitas dengan metode purposive sampling, kriteria yang digunakan yaitu karyawan tetap (Permanent/PKWTT) dengan masa kerja lebih dari 5 tahun Hasil penelitian menunjukkan bahwa proses manajemen pengetahuan yang dilihat dari knowledge protection berpengaruh positif dan tidak signifikan terhadap kinerja karyawan PT. Mitra Kerinci.